Food chemistry a laboratory manual - Miller, Dennis D. 1945-; Yeung, C. K. (Hoboken, New Jersey John Wiley & Sons, Inc., 2022)
"Food chemistry is the study of the chemistry of foods, their deterioration, and the principles underlying the improvement of foods for the consuming public. It is the application of chemistry to the development, processing, packaging, preservation, storage, and distribution of foods and beverages for the purposes of obtaining a safe, economical, and aesthetically pleasing supply of food for people worldwide"--
Includes bibliographical references and index.
Keywords: Food -- Analysis -- Laboratory manuals; Food -- Composition -- Laboratory manuals